2017
DOI: 10.1016/j.neuron.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Netrin1 Produced by Neural Progenitors, Not Floor Plate Cells, Is Required for Axon Guidance in the Spinal Cord

Abstract: SUMMARY Netrin1 has been proposed to act from the floor plate (FP) as a long-range diffusible chemoattractant for commissural axons in the embryonic spinal cord. However, netrin1 mRNA and protein are also present in neural progenitors within the ventricular zone (VZ), raising the question of which source of netrin1 promotes ventrally-directed axon growth. Here, we use genetic approaches in mice to selectively remove netrin from different regions of the spinal cord. Our analyses show that the FP is not the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
193
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(225 citation statements)
references
References 46 publications
19
193
1
3
Order By: Relevance
“…Since Netrin-1 is one of major attractive guidance cues produced both by the floor plate (Kennedy et al, 2006; Serafini et al, 1996) and by neural progenitors that constitute the ventral and lateral tissues in the neural tube (Dominici et al, 2017; Varadarajan et al, 2017), we tested if attractive Netrin-1/DCC signals are involved in guiding motor exit points to their proper position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Netrin-1 is one of major attractive guidance cues produced both by the floor plate (Kennedy et al, 2006; Serafini et al, 1996) and by neural progenitors that constitute the ventral and lateral tissues in the neural tube (Dominici et al, 2017; Varadarajan et al, 2017), we tested if attractive Netrin-1/DCC signals are involved in guiding motor exit points to their proper position.…”
Section: Resultsmentioning
confidence: 99%
“…(Dominici et al, 2017; Hand and Kolodkin, 2017; Varadarajan et al, 2017). However, distinguishing the crucial source of Netrin-1 cue was not possible with the global Netrin-1 mutant that we used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested a local, adhesive role for netrin, attaching growth cones to source cells in the developing medulla (Akin and Zipursky, 2016). Moreover, our recent studies in the spinal cord (Varadarajan et al, 2017), with those in the hindbrain (Dominici et al, 2017), have revisited the role of FP-derived netrin1 in axon guidance. In the mouse spinal cord, both neural progenitor cells (NPCs) in the ventricular zone (VZ), and FP cells express netrin1 (Serafini et al, 1996) and netrin1 protein decorates both commissural axons and the pial (basal) margin of the spinal cord (Kennedy et al, 2006; Varadarajan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Netrin-1 is expressed at the midline of the developing CNS and acts as an attractive or repulsive cue for different populations of crossing/commissural axons (2). The classical view that attraction of commissural axons is mediated by a gradient of floor-plate-derived netrin-1 has been recently challenged: netrin-1 primarily acts locally by promoting growth cone adhesion (3,4). In netrin-1-KO mice, many commissural axons fail to cross the midline in the corpus callosum, the hippocampal and anterior commissures, the corticospinal tract (CST), and the spinal cord (5-7).…”
Section: Introductionmentioning
confidence: 99%